Peran Manajemen Sumber Daya Manusia dalam Diakonia di Era Digital - Andiny, Tiavone Theressa (Institut Agama Kristen Negeri Palangka Raya, 2023)
Entering the era of society 5.0 where digital technology is experiencing an increasingly rapid evolution in the midst of global competition, the Church in carrying out its services utilizes digital technology to provide information through social media, including during worship, requires human resources who understand and are able to run multimedia or IT (Information and Technology). The purpose of writing is to analyze in depth the Role of HR Management in Diakonia in the Digital Age. The method used in this writing is literature study, namely analyzing and classifying facts collected from research results such as journals, books, magazines, newspapers, and online databases. In conclusion, the Church in the modern era must be able to adapt and have the courage to make breakthroughs in diakonia. Through the role of HR Management who are capable and willing to develop themselves so they can innovate. Memasuki era society 5.0 dimana teknologi digital mengalami evolusi yang semakin pesat di tengah persaingan global, Gerejapun dalam melaksanakan pelayanannya memanfaatkan teknologi digital untuk memberikan informasi melalui media sosial, termasuk saat pelaksanaan ibadah, dibutuhkan SDM yang mengerti dan mampu menjalankan multimedia ataupun IT (Information and Technology). Tujuan penulisan ialah menganalisa secara mendalam mengenai Peran Manajemen SDM dalam Diakonia di Era Digital. Metode yang digunakan dalam penulisan ini adalah studi kepustakaan, yakni melakukan analisis dan klasifikasi fakta yang dikumpulkan dari hasil-hasil penelitian seperti jurnal, buku, majalah, koran, maupun online database. Kesimpulan, Gereja di era modern harus mampu beradaptasi dan berani membuat terobosan dalam diakonia. Melalui Peran Manajeman SDM yang cakap dan mau mengembangkan diri agar dapat berinovasi.